Phylogeographic pattern and extensive mitochondrial DNA divergence disclose a species complex within the Chagas disease vector Triatoma dimidiata. - Fernando A Monteiro (Public Library of Science (PLoS), 2013)
Background Triatoma dimidiata is among the main vectors of Chagas disease in Latin America. However, and despite important advances, there is no consensus about the taxonomic status of phenotypically divergent T. dimidiata populations, which in most recent papers are regarded as subspecies. Methodology and findings A total of 126 cyt b sequences (621 bp long) were produced for specimens from across the species range. Forty-seven selected specimens representing the main cyt b clades observed (after a preliminary phylogenetic analysis) were also sequenced for an ND4 fragment (554 bp long) and concatenated with their respective cyt b sequences to produce a combined data set totalling 1175 bp/individual. Bayesian and Maximum-Likelihood phylogenetic analyses of both data sets (cyt b, and cyt b+ND4) disclosed four strongly divergent (all pairwise Kimura 2-parameter distances >0.08), monophyletic groups: Group I occurs from Southern Mexico through Central America into Colombia, with Ecuadorian specimens resembling Nicaraguan material; Group II includes samples from Western-Southwestern Mexico; Group III comprises specimens from the Yucatán peninsula; and Group IV consists of sylvatic samples from Belize. The closely-related, yet formally recognized species T. hegneri from the island of Cozumel falls within the divergence range of the T. dimidiata populations studied. Conclusions We propose that Groups I-IV, as well as T. hegneri, should be regarded as separate species. In the Petén of Guatemala, representatives of Groups I, II, and III occur in sympatry; the absence of haplotypes with intermediate genetic distances, as shown by multimodal mismatch distribution plots, clearly indicates that reproductive barriers actively promote within-group cohesion. Some sylvatic specimens from Belize belong to a different species - likely the basal lineage of the T. dimidiata complex, originated ~8.25 Mya. The evidence presented here strongly supports the proposition that T. dimidiata is a complex of five cryptic species (Groups I-IV plus T. hegneri) that play different roles as vectors of Chagas disease in the region.